A Case Series of Laparoscopic Colorectal Resections with Natural Orifice Specimen Extraction and Systematic Literature Review - Ahmad, Nasir Zaheer; Swayamjoti, Ray; Flashman, Karen; Naqvi, Syed Abul Hassan; Khan, Jim (The Surgery Journal, 2021)
Background Minimal access surgery is associated with improved cosmetic and other short-term outcomes. Conventionally, an abdominal incision is made for specimen extraction. We assessed the feasibility of specimen extraction through one of the natural orifices and analyzed its impact on short-term outcomes.Methods A prospectively collected data were reviewed on consecutive patients who underwent natural orifice specimen extraction (NOSE) after laparoscopic colorectal surgery. The results were compared with a matched group who had transabdominal extraction (TAE) of the specimens. A systematic literature review was performed to compare our results.Results The combined median operating time for right and left colectomies was significantly higher in the NOSE group as compared with TAE group (260 vs. 150). There was no mortality in either group and no conversions to TAE in the NOSE group. No local metastasis or major iatrogenic injuries were reported at the time of retrieval. The results were comparable to those of a meta-analysis of randomized controlled trials.Conclusion The results of NOSE are comparable to those of TAEs. The absence of a minilaparotomy for specimen extraction may lead to a speedy recovery and better cosmesis.
Keywords: minimal access surgery; natural orifice specimen extraction; cosmetic